A Study of Exclusive Breastfeeding History and Animal Protein Consumption in Stunted Toddlers - Oktavia, Arini; Andrestian , Meilla Dwi; Rahmani (Jurnal Riset Pangan dan Gizi, 2025)
Stunting is a chronic nutritional problem that remains a major public health concern, especially among toddlers. One of the prevention efforts is through adequate exclusive breastfeeding and sufficient animal protein intake during the growth period. The working area of Landasan Ulin Public Health Center reports a relatively high stunting prevalence, exceeding the national target, with suboptimal coverage of exclusive breastfeeding and animal protein consumption. This study aims to describe the history of exclusive breastfeeding and animal protein consumption among stunted toddlers in this area. This research used a descriptive observational method with a quantitative approach. The population included all stunted toddlers aged 24–59 months in the Landasan Ulin working area, totaling 176 children. A sample of 71 toddlers was selected using proportional simple random sampling. Data were collected through interviews using a questionnaire and analyzed univariately. The results showed that 56.3% of stunted toddlers received exclusive breastfeeding, and 70.4% had moderate levels of animal protein intake. Meanwhile, 43.7% were not exclusively breastfed, and 28.2% had low animal protein intake. Parents are expected to improve their knowledge and practices regarding exclusive breastfeeding for the first 6 months and ensure sufficient animal protein intake to support optimal growth and prevent stunting.